EARTHQUAKE PREPAREDNESS OF SELECTED POLICE STATIONS IN METRO MANILA, PHILIPPINES: TOWARDS OPERATIONAL CAPABILITIES - Genaro P Mancio, Renel P Cruz, Edelito P Deles, PhD.3, Oscar G Abuan, (EPRA International Journal of Multidisciplinary Research (IJMR), 2024)
This study employed quantitative research methods to evaluate the level of earthquake preparedness in selected police stations located in Metro Manila. The study examined four crucial aspects: Organization and Planning, Resources and Logistics, Coordination and Responsiveness, and Training. Information was gathered from two cohorts: 207 law enforcement officers stationed at the designated police stations and 200 individuals from the general population living in Metro Manila. The study utilized a survey questionnaire that applied a four-point rating scale, ranging from "Highly Prepared" to "Not Prepared," to assess the perceptions of both groups regarding the preparedness of these police stations. The findings revealed a significant disparity in the perception of earthquake readiness between police personnel and the civilian population at the selected stations. Police personnel usually maintained a favorable perspective, considering their stations well-equipped and competent, whereas the civilian populace reported lower confidence in their preparedness. This difference in perception highlights the necessity for enhanced communication, education, and community involvement to close the gap and increase public knowledge of the earthquake preparedness initiatives of police stations in Metro Manila. Hence, the research suggests prioritizing teaching programs for police personnel and cultivating closer ties with local people to establish confidence and enhance earthquake preparedness endeavors. Overall, this study provides significant knowledge about the earthquake readiness situation in specific police stations in Metro Manila. This information has implications for improving disaster management strategies and initiatives, ultimately leading to more efficient preparedness and response efforts in the event of earthquakes in the region.